The teaching or nursing in Spain during the 17th century. Simon Lopez´s manual (1668) - Manuel Jesús García Martínez; Antonio Claret García Martínez (Universidad de Alicante, 1998)
The aim of the present study is to clearly state what nursing functions and tasks were in force in Spain in the 17th c. with emphasis on the teaching of nursing. The method used here has been based on the historical analysis of Simón López's Manual: «Guidelines for nurses and volunteers for the caring of body illnesses» (1668). The following conclusions have been reached: Simón López's work shows the existence of the four nursing functions which are recognized in nursing nowadays: care, teaching, administration and research. López's work accurately describes the teaching activities carried out during that period. His text has been considered a key piece in the understanding of Spanish nursing in the 17th c.